2015
DOI: 10.1002/2014jf003331
|View full text |Cite
|
Sign up to set email alerts
|

Validation of DEM prediction for granular avalanches on irregular terrain

Abstract: Accurate numerical simulation can provide crucial information useful for a greater understanding of destructive granular mass movements such as rock avalanches, landslides, and pyroclastic flows. It enables more informed and relatively low cost investigation of significant risk factors, mitigation strategy effectiveness, and sensitivity to initial conditions, material, or soil properties. In this paper, a granular avalanche experiment from the literature is reanalyzed and used as a basis to assess the accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…This reaffirms the point that porosity alone is not an adequate measure of system rheology. For example, Mead and Cleary [] demonstrated that modeling granular avalanches could only replicate natural examples if nonspherical particles were used. Yamamoto and Matsuoka [] and Kawabata et al .…”
Section: The Dynamics Of Hydrogranular Mediasupporting
confidence: 86%
See 1 more Smart Citation
“…This reaffirms the point that porosity alone is not an adequate measure of system rheology. For example, Mead and Cleary [] demonstrated that modeling granular avalanches could only replicate natural examples if nonspherical particles were used. Yamamoto and Matsuoka [] and Kawabata et al .…”
Section: The Dynamics Of Hydrogranular Mediasupporting
confidence: 86%
“…This reaffirms the point that porosity alone is not an adequate measure of system rheology. For example, Mead and Cleary [2015] demonstrated that modeling granular avalanches could only replicate natural examples if nonspherical particles were used. Yamamoto and Matsuoka [1997] and Kawabata et al [2013] demonstrated how plate-like particles, a common shape of natural crystals, leads to distinct microstructures, shear banding, and kinematic features reminiscent of geological examples.…”
Section: Nonspherical Particlesmentioning
confidence: 99%
“…Conversely, models of geophysical flows that ignore their granular nature (such as multiphase and depthaveraged models) are unable to predict the flow runouts even with the correct parameter values. Studies of granular flows by means of discrete element modeling include Valentino et al (2008), Banton et al (2009), Girolami et al (2012, Yohannes et al (2012), Mollon et al (2012), Cagnoli and Piersanti (2015) and Mead and Cleary (2015).…”
Section: Introductionmentioning
confidence: 99%
“…These polyhedrons represent an equant, an oblate and a prolate particle, respectively. Nonspherical particles are preferred because when interacting amongst themselves and with the boundary surfaces, their energy dissipation mechanism (due to collisions and attrition) is comparable with that of natural fragments since they are both angular (Cagnoli and Romano, 2012a;Mead and Cleary, 2015). The proportion of each particle shape is always the same in all flows irrespective of grain size, flow mass or channel features: the equant particles are 38 %, the oblate particles 22 % and the prolate particles 40 % of the flow mass.…”
Section: Introductionmentioning
confidence: 99%
“…This is simply untrue. The soft-particle discrete element technique has been tested against numerous laboratory experiments [e.g., Mead and Cleary, 2015]. (And while Iverson seems to have a high opinion of the Mead and Cleary simulations, their results merely show that discrete element model simulations can closely match one of Iverson's experiments; they reveal nothing about mechanics of long runout landslides.)…”
Section: Landslide Dynamics Testing Models and Diverse Datamentioning
confidence: 99%